Towards a History of Mountain Runaways“Migrants” and the Genealogies of Mountain Rescue and Struggles - Martina Tazzioli (Revue de Géographie Alpine)
This paper looks at current migrant crossing on the Alps from the standpoint of a history of runaways. It interrogates the traces left by the recent migrants’ fleeting presence at the Northern French-Italian Alpine border situating these in connection with both the memory of past migrants’ passages and with mountain rescue practices and solidarity networks that have shaped those Alpine valleys. It starts with a section on mobile infrastructures of solidarity deployed at the French-Italian Alpine border, retracing its brief history as well as of the sedimented memory of the struggles in the Susa Valley. The paper moves on with a section about the history of mountain rescue at the French-Alpine border, showing how foreigners and also Italian “clandestine emigrants” were rescued there in the past. It concludes by advancing a history of mountain runaways as an analytical framework to politicise migrants’ passages on the Alps.